Sweet bakery products for diabetic’s diet and analysis of risk associated with selected ingredients - Slavica Grujić; Božana Odžaković (Journal of Engineering & Processing Management, 2021)
Diabetes is a complex, chronic illness that demands a healthy diet. The overall quality of consumed food is important for diabetics, but benefits are expected from whole grains and lower-energy food. Choice of appropriate sweet bakery product may present the problem for diabetics in meal planning. The aim of this research is to provide an overview of some opportunities for new food product development for persons with diabetes and to analyze the risks associated with selected food ingredients, which can be used. It includes identification of special requirements for controlled nutrition. Quality parameters and food product composition are determined on a formulation for muffins modified to contain ingredients recommended and safe for diabetics' diet with lower energy value, but keeping prescribed and acceptable product quality. The research focuses on assessment of the risks analysis associated with selected ingredients on an example of muffin-like cake formulation modelling and use of wheat flour, sugars, fats, salt and some additional ingredients, milk, eggs and cocoa powder, based on experience, insight into recommendations for diabetics’ nutrition and scientifically identified indicators aimed at health protection. Methodology for the selection of the ingredients for energy-reduced muffin-like cakes with whole-grain wheat flour and cocoa, suitable for diabetics’ diet presented in the paper, can be used as a model for developing other products aimed to improve nutrition of persons with healthy food preferences or diseases. In addition, it presents an opportunity for the food industry contribution to healthy lifestyle by developing products adapted to modern dietary recommendations and target consumers group.
Keywords: diabetics’ diet; energy-reduced cakes; selection ingredients; risks analysis